A New Computer Survey System - Uchino, Takao (The International Hydrographic Review, 2015)
To cope with the increasing demand for hydrographic surveys as well as to improve the quality of survey results involving huge amounts of data, the best way seems to be to introduce an automated system into each process. This would further be effective in solving the problem of shortage of skilled surveyors now faced in this sector. The system presented in this paper, which is still being evaluated, has been developed on the basis of the above considerations. The data are automatically acquired aboard a survey ship, while the capabilities of electronic computers and automatic drafters ashore are fully utilized for better efficiency and accuracy in processing survey data as well as in drafting smooth sheets.